Disseminated cutaneous histoplasmosis in elderly patients. An uncommon presentation - Marques, Silvio Alencar [UNESP]; Hortense, Juliana [UNESP]; Requena, Camila Bueno [UNESP]; Camargo, Rosangela Maria Pires de [UNESP]; Marques, Mariangela Esther Alencar [UNESP] (Elsevier, 2015)
Background: Human fungal infections have increased at an alarming rate in recent years, particularly in immunocompromised individuals. Cryptococcosis is the second most prevalent systemic fungal infection worldwide, and the most prevalent systemic infection in immunocompromised individuals, representing more than 70% of cases. The incidence of cryptococcosis is high in people with HIV/acquired immunodefi- ciency syndrome (AIDS), with recent estimates indicating that there are one million cases of cryptococcal meningitis globally per year in AIDS patients. Aims: The aim of this research was to develop a rapid flow cytometric antifungal susceptibility test and to compare the results with the standard methods. Methods: A reference strain and clinical isolates of Cryptococcus neoformans and Cryptococcus gattii were tested for susceptibility to amphotericin B by flow cytometry using propidium iodide as indicator of viability. Flow cytometry (FC) results were compared with the minimum inhibitory concentration (MIC) values determined by microdilution. Results: The antifungal activity of amphotericin B ranged from MICs of 0.06 to 2 g/ml for the 11 isolates studied. The same results were found by FC. Conclusions: The FC method allows same-day results, assisting in the selection of appropriate antifungal therapies. These results demonstrate an excellent correlation between FC and the classic methods of testing for susceptibility to antifungal agents. This rapid diagnosis method makes it possible to quickly administer effective therapeutic interventions, often saving lives.
Histoplasmosis cutánea diseminada en un paciente mayor. Una presentación poco común